1974
DOI: 10.1055/s-0028-1093819
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Proinsulin-Like Material in Insulin Treated Diabetics

Abstract: Plasma sampies from 14 insulin treated diabetic subjects were subjected to Sephadex gel filtration before and after acid-alcohol extraction. The findings were consistent with the presence of insulin antibodies, which on dissociation, released !arge amounts of immunoreactive material, eluting in positions consistent with proinsulin-like material (PLM) as weil as insulin. Because the percentages of PLM were high (compatible with values seen in patients with islet cell tumors), the sources of this material were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

1976
1976
1988
1988

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 4 publications
2
12
0
Order By: Relevance
“…In agreement with the previous reports (Block et al, 1972 ;Fink et al, 1974), a large amount of PLC was Fig. 4.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with the previous reports (Block et al, 1972 ;Fink et al, 1974), a large amount of PLC was Fig. 4.…”
Section: Resultssupporting
confidence: 93%
“…However, insulin-treated diabetics were found to have rather higher CPR levels than healthy subjects (Block et al, 1972). The sera of insulin-treated diabetics were also found to contain a large amount of proinsulin-like components (PLC) (Block et al, 1972;Fink et al, 1974). As these diabetics had circulating insulin antibodies, it was supposed that the secreted PLC was bound to insulin antibodies and accumulated in the circulation.…”
Section: Synopsismentioning
confidence: 99%
“…This leads to an accumulation of proinsulin in plasma due to the prolonged disappearance time of the proinsulin-antibody complexes. 16 It also reduces the effectivity of the solid-phase-antibody removal of proinsulin. If significant amounts of human proinsulin had been codetermined in these 17 patients an inverse correlation between the insulin-antibody level, as determined by the insulin binding to IgG, and relative C-peptide increase would have been expected.…”
Section: Maximum C-peptide Increasementioning
confidence: 99%
“…However, in the latter study, human Acta Paediatr Srand Suppl270 proinsulin was not removed prior to the determination of C-peptide and this may have resulted in an overestimation of the C-peptide values. It has been reported that human proinsulin may constitute an extremely high proportion of the CPR in insulin treated diabetics, in all probability mainly because of the binding of proinsulin to the insulin antibodies (2,4,10). The purpose of the present study was to determine the concentration of human proinsulin in a group of insulin-treated juvenile diabetics and to compare the results of this study with the results obtained in a group of adult insulin requiring diabetics (1 1).…”
mentioning
confidence: 81%